The Alternative Oxidase AOX Does Not Rescue the Phenotype of tko(25t) Mutant Flies - Kemppainen, Kia K. (Genetics Society of America, 2014)
A point mutation [technical knockout(25t) (tko(25t))] in the Drosophila gene coding for mitoribosomal protein S12 generates a phenotype of developmental delay and bang sensitivity. tko(25t) has been intensively studied as an animal model for human mitochondrial diseases associated with deficiency of mitochondrial protein synthesis and consequent multiple respiratory chain defects. Transgenic expression in Drosophila of the alternative oxidase (AOX) derived from Ciona intestinalis has previously been shown to mitigate the toxicity of respiratory chain inhibitors and to rescue mutant and knockdown phenotypes associated with cytochrome oxidase deficiency. We therefore tested whether AOX expression could compensate the mutant phenotype of tko(25t) using the GeneSwitch system to activate expression at different times in development. The developmental delay of tko(25t) was not mitigated by expression of AOX throughout development. AOX expression for 1 d after eclosion, or continuously throughout development, had no effect on the bang sensitivity of tko(25t) adults, and continued expression in adults older than 30 d also produced no amelioration of the phenotype. In contrast, transgenic expression of the yeast alternative NADH dehydrogenase Ndi1 was synthetically semi-lethal with tko(25t) and was lethal when combined with both AOX and tko(25t). We conclude that AOX does not rescue tko(25t) and that the mutant phenotype is not solely due to limitations on electron flow in the respiratory chain, but rather to a more complex metabolic defect. The future therapeutic use of AOX in disorders of mitochondrial translation may thus be of limited value.